преобразовать

(1)/(2) + ( (3m)/(1-3m) + (2m)/(3m+1) ) * (9m^(2)-6m+1)/(6m^(2)+10m)

распишите не только ответ а решение тоже пожалуйста

1

Ответы и объяснения

2011-04-12T12:02:00+04:00

1/2 +  (3m * ( 1+3m) +2m * (1 -3m))/ (1-9m^2) * (3m-1)^2 / (2m*(3m+5) =

1/2 + (3m+9m^2+2m-6m^2)/(1-9m^2) * (3m-1)^2 /2m(3m+5) =

1/2 + (5m+3m^2)/ (1-9m^2) * (3m-1)^2 / 2m (3m+5) =

1/2 + (m*95+3m)*(3m-1)^2 )/ (2m(3m+5)*(1-9m^2) =

1/2+(3m-1)^2 / (-2 *( 3m-1)(1+3m))

= 1/2+ (3m-1)/(-2(1+3m)) = (-(1+3m)+3m-1))/(-2(1+3m)) = (-2)/(-2(1+3m) = 1/ (1+3m)

 

у меня так получилось)